2(x+1)-3(x-2)=x-2

Simple and best practice solution for 2(x+1)-3(x-2)=x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+1)-3(x-2)=x-2 equation:


Simplifying
2(x + 1) + -3(x + -2) = x + -2

Reorder the terms:
2(1 + x) + -3(x + -2) = x + -2
(1 * 2 + x * 2) + -3(x + -2) = x + -2
(2 + 2x) + -3(x + -2) = x + -2

Reorder the terms:
2 + 2x + -3(-2 + x) = x + -2
2 + 2x + (-2 * -3 + x * -3) = x + -2
2 + 2x + (6 + -3x) = x + -2

Reorder the terms:
2 + 6 + 2x + -3x = x + -2

Combine like terms: 2 + 6 = 8
8 + 2x + -3x = x + -2

Combine like terms: 2x + -3x = -1x
8 + -1x = x + -2

Reorder the terms:
8 + -1x = -2 + x

Solving
8 + -1x = -2 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
8 + -1x + -1x = -2 + x + -1x

Combine like terms: -1x + -1x = -2x
8 + -2x = -2 + x + -1x

Combine like terms: x + -1x = 0
8 + -2x = -2 + 0
8 + -2x = -2

Add '-8' to each side of the equation.
8 + -8 + -2x = -2 + -8

Combine like terms: 8 + -8 = 0
0 + -2x = -2 + -8
-2x = -2 + -8

Combine like terms: -2 + -8 = -10
-2x = -10

Divide each side by '-2'.
x = 5

Simplifying
x = 5

See similar equations:

| 36=12/x | | 3x=(x+8)(x-4) | | 2z^3-6z^2-920=0 | | 10x-18x=4 | | 21+y=17 | | 14w=91. | | 3ex-1=75 | | y=-6(x-18) | | 3u-12=12 | | .5x+2.5=-6 | | 6x-11=61-3x | | 13x+3=-23 | | y+8=28 | | 5x+12=3x+13 | | z+6=15 | | 3x+27=12x+13 | | 7x-2=6x+1 | | 360=127+53+127+-2+5x | | y/2=2 | | (-10x-7)-(3x-10)= | | (10x-7)-(3x-10)= | | 4b^3-12b^2-832b=0 | | 14y=126 | | 360=145+66+63+x+57 | | 3g-6=12 | | 3g-6=-12 | | 9x^2-72x-16y^2-3y-16=0 | | 15-z=1 | | 360=100+66+45+12x-7 | | Z+3x-2+z-5x+7= | | 4x/7-x | | 12(x+8)=8*30 |

Equations solver categories